2009
DOI: 10.1007/s10658-008-9427-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an artificial reaction control in a TaqMan method for PCR detection of Ralstonia solanacearum race 3 biovar 2

Abstract: A previously published TaqMan PCR test for R. solanacearum race 3 biovar 2 was modified to enable both the validation of negative results and the confirmation of positive results in a closed-tube system. Negative results were validated through the use of a reaction control plasmid, designated pRB2C2, which was designed to generate a 94bp product using the same amplimers targeting the primary diagnostic 68bp sequence in R. solanacearum race 3 biovar 2 DNA. SYBR Green was included in the reaction mix to facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The modified TaqMan assay procedure, developed in this investigation, successfully detected Rs race 3 bv. 2 in infected asymptomatic tomato stems and leaves of tomato, as well as in potato tubers and stems (Smith and De Boer 2009).…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 96%
“…The modified TaqMan assay procedure, developed in this investigation, successfully detected Rs race 3 bv. 2 in infected asymptomatic tomato stems and leaves of tomato, as well as in potato tubers and stems (Smith and De Boer 2009).…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 96%
“…The real-time TaqMan PCR assay of Smith and De Boer (2009) with internal control was used to compare with a real-time PCR assay originally described by Ozakman and Schaad (2003). Both assays are used for detecting R. solanacearum R3bv2 in asymptomatic potato tubers.…”
Section: Detection By Real-time Taqman Pcr Assaysmentioning
confidence: 99%
“…However, the two assays differed in sensitivity (Table 3). The assay based on TaqMan chemistries with internal control (Pastrik et al 2000;Smith and De Boer 2009) showed the highest sensitivity (Tables 3 and 4, gel images see supporting materials), detecting spiked concentration of 68, 86 and 120 CFU ml À1 for R3bv2 strains NCPPB339, B0167 and NCPPB909, respectively. The detection limit for 15 other R3bv2 strains was at a similar range.…”
Section: Specific Assays For Detection Of Ralstonia Solanacearum R3bvmentioning
confidence: 99%
See 1 more Smart Citation
“…Grover et al . () used MDA‐PCR to detect ultra‐low populations; Smith and de Boer () developed an improved TaqMan method for PCR; Poussier et al . (), Alvarez Restrepo et al .…”
Section: Specific Groups Of Exotic Pathogensmentioning
confidence: 99%